Transient isolated brainstem symptoms preceding posterior circulation stroke: a population-based study - Paul, Nicola LM (Lancet Pub. Group, 2013)
BACKGROUND: Transient isolated brainstem symptoms (eg, isolated vertigo, dysarthria, diplopia) are not consistently classified as transient ischaemic attacks (TIAs) and data for prognosis are limited. If some of these transient neurological attacks (TNAs) are due to vertebrobasilar ischaemia, then they should be common during the days and weeks preceding posterior circulation strokes. We aimed to assess the frequency of TNAs before vertebrobasilar ischaemic stroke. METHODS: We studied all potential ischaemic events during the 90 days preceding an ischaemic stroke in patients ascertained within a prospective, population-based incidence study in Oxfordshire, UK (Oxford Vascular Study; 2002–2010) and compared rates of TNA preceding vertebrobasilar stroke versus carotid stroke. We classified the brainstem symptoms isolated vertigo, vertigo with non-focal symptoms, isolated double vision, transient generalised weakness, and binocular visual disturbance as TNAs in the vertebrobasilar territory; atypical amaurosis fugax and limb-shaking as TNAs in the carotid territory; and isolated slurred speech, migraine variants, transient confusion, and hemisensory tingling symptoms as TNAs in uncertain territory. FINDINGS: Of the 1141 patients with ischaemic stroke, vascular territory was categorisable in 1034 (91%) cases, with 275 vertebrobasilar strokes and 759 carotid strokes. Isolated brainstem TNAs were more frequent before a vertebrobasilar stroke (45 of 275 events) than before a carotid stroke (10 of 759; OR 14·7, 95% CI 7·3–29·5, p<0·0001), particularly during the preceding 2 days (22 of 252 before a vertebrobasilar stroke vs two of 751 before a carotid stroke, OR 35·8, 8·4–153·5, p<0·0001). Of all 59 TNAs preceding (median 4 days, IQR 1–30) vertebrobasilar stroke, only five (8%) fulfilled the National Institute of Neurological Disorders and Stroke (NINDS) criteria for TIA. The other 54 cases were isolated vertigo (n=23), non-NINDS binocular visual disturbance (n=9), vertigo with other non-focal symptoms (n=10), isolated slurred speech, hemisensory tingling, or diplopia (n=8), and non-focal events (n=4). Only 10 (22%) of the 45 patients with isolated brainstem TNAs sought medical attention before the stroke and a vascular cause was suspected by their physician in only one of these cases. INTERPRETATION: In patients with definite vertebrobasilar stroke, preceding transient isolated brainstem symptoms are common, but most symptoms do not satisfy traditional definitions of TIA. More studies of the prognosis of transient isolated brainstem symptoms are required. FUNDING: Wellcome Trust, UK Medical Research Council, Dunhill Medical Trust, Stroke Association, National Institute for Health Research (NIHR), Thames Valley Primary Care Research Partnership, and the NIHR Biomedical Research Centre, Oxford.